Storming the Cubicle. - Neville-Neil, George V. (Communications of the ACM, 2015)
The article presents questions and answers related to computer programming including the importance of using warning messages when writing software code and the process of reviewing software from a potential company acquisition in terms of the intellectual property rights associated with that software.